Investigating Money Political Crimes in 2018 Simultaneous Elections (Case Study in Kuningan District and Ternate District) - Iryanto, Wisnu Pratama (Law Research Review Quarterly, 2018)
The 2018 simultaneous local elections have taken place with several traces of criminal cases taking place. The Election Supervisory Agency noted that there were 291 reports and findings of criminal violations during the 2018 Simultaneous Election. 52 cases had been brought to court with two cases related to money politics by a pair of candidates in two districts namely Kuningan and Ternate. In the case of Kuningan, the perpetrators were sentenced to 3 years in prison and fined 200 million rupiah. While in Ternate, there are two cases of money politics whose cases are still being tried. The research method used in the writing of this paper is based on the study of literature. The study in this research focuses on the process of the occurrence of money politics that leads to criminal acts. In addition, this study also outlines the criteria for the occurrence of money politics, criminal sanctions, as well as examples of case studies that occurred in the 2018 Simultaneous Local Election.